Trace metal levels in abdominal muscle tissue of freshwater crayfish (Astacus leptodactylus Eschscholtz, 1823) from Iznik Lake, Bursa, Turkey - (:unkn) unknown (Parlar Scientific Publications, 2015)
The freshwater crayfish (Astacus leptodactylus Eschscholtz, 1823) is a valuable and protected invertebrate species and the only native and dominant species in the big lakes of Turkey, such as Iznik Lake (Bursa, Turkey). In this study, bioaccumulation of some heavy metals (Zn, Cu, Cd, Pb) in abdominal muscle tissue of Astacus leptodactylus samples collected between November 2008 and December 2009 was examined. Heavy metal contents in muscle tissues were measured by AAS analysis. According to the obtained data, the levels of Zn, Cu, Cd and Pb for the studied samples were within normal ranges, and lower than all the recommended legal limits. The descending order of heavy metal concentrations found in crayfish is Zn>Cu>Cd>Pb. Heavy metal concentrations in freshwater crayfish samples were compared with the maximum permitted levels of heavy metals in seafood regulated by the EU, FAO and Turkish Food Codex limits. The results showed that there was no serious hazard in the samples in terms of the Zn, Cu, Cd and Pb values analyzed from Iznik Lake, Bursa, Turkey. © by PSP.
Keywords: Astacus leptodactylus; Iznik Lake; Pollution; Trace metals